Nickel hyperaccumulation, elemental profiles and agromining potential of three species of Odontarrhena from the ultramafics of Western Iran. Issue 3 (23rd February 2023) - Ghafoori, Mohammad; Shariati, Mansour; van der Ent, Antony; Baker, Alan J. M.
Abstract: The profiles of trace and major elements in three Odontarrhena species from the ultramafics of Western Iran ( O. callichroa, O. penjwinensis and O. inflata ) were evaluated to provide detailed information on their soil-plant relationships and potentials for agromining. The mean concentrations of Ni in leaf dry matter of these three species were 877, 3, 270 and 2, 720 mg kg −1, respectively. The mean concentrations of total soil Ni at sites Mazi Ban, Kamyaran and Ghala Ga were 1, 470, 2, 480, 1, 030 mg kg −1, respectively. The Bioconcentration Factor (BCF) for Ni was >1 in O. penjwinensis and O. inflata, but not in O. callichroa . A positive relationship between shoot Ni and soil pH was found for all three species. They display Ni hyperaccumulation in the leaves, but with pronounced variation in the Ni concentrations attained. Odontarrhena penjwinensis emerged as the most promising potential candidate for future Ni agromining. The progress made in this study will enable further consideration of the three Odontarrhena species, especially O. penjwinensis, for any future commercial Ni agromining of the serpentinic ultramafic soils in Western Iran. NOVELTY STATEMENT: This pioneering study in a remote part of Western Iran is the first to evaluate nickel hyperaccumulating species of Odontarrhena ( Alyssum ) in relation to their soil-plant relationships and potential for agromining.